2022
DOI: 10.31234/osf.io/n5d9h
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of the “take time to think” safer gambling message: a randomised, online experimental study

Abstract: Safer gambling messages can potentially form a part of a public health approach to preventing gambling-related harms, if found effective. This study tested the effect of the new UK safer gambling message, “take time to think”, on a range of gambling behaviours in a sample of UK-based online gamblers. UK-based online gamblers could earn monetary endowments during an initial task, which they then had the option to gamble with on a commercially available online roulette game. Participants could quit the game, eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Gambling adverts also typically contain safer gambling messages (S. Davies et al, 2022). At the time that the men's EURO 2020 tournament aired, the main UK safer gambling message was "when the fun stops, stop" (van Schalkwyk et al, 2021), as the new message "take time to think" was unveiled only a few months later in October 2021 (Newall, Hayes, et al, 2022).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Gambling adverts also typically contain safer gambling messages (S. Davies et al, 2022). At the time that the men's EURO 2020 tournament aired, the main UK safer gambling message was "when the fun stops, stop" (van Schalkwyk et al, 2021), as the new message "take time to think" was unveiled only a few months later in October 2021 (Newall, Hayes, et al, 2022).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Gambling adverts also typically contain safer gambling messages (Davies et al, 2022). At the time that the men's EURO 2020 tournament aired, the main UK safer gambling message was "when the fun stops, stop" (van Schalkwyk et al, 2021), as the new message "take time to think" was unveiled only a few months later in October 2021 (Newall, Hayes, et al, 2022). We thought it was important to track the prevalence of the "when the fun stops, stop" message, as previous research has indicated its prevalence in other forms of UK gambling marketing (Critchlow et al, 2020), as well of its lack of beneficial effect on concurrent gambling expenditure .…”
Section: Introductionmentioning
confidence: 99%
“…Pop-up messages that involve cognitive tasks can interrupt dissociation during game play [23]. However, the direction of the impact depends on the size and design of messages [24,25]. Thus, both message content and how the message is conveyed play critical roles in affecting gambler behavior, leading to bene cial or harmful results [26].…”
Section: Introductionmentioning
confidence: 99%
“…Gambling adverts also typically contain safer gambling messages (S. Davies et al, 2022). At the time that the men's EURO 2020 tournament aired, the main UK safer gambling message was "when the fun stops, stop" (van Schalkwyk et al, 2021), as the new message "take time to think" was unveiled only a few months later in October 2021 (Newall, Hayes, et al, 2022). We thought it was important to track the prevalence of the "when the fun stops, stop" message, as previous research has indicated its prevalence in other forms of UK gambling marketing (Critchlow et al, 2020), as well of its lack of beneficial effect on concurrent gambling expenditure .…”
mentioning
confidence: 99%